Evaluasi Penggunaan Antibiotik pada Penderita Diabetes Melitus Tipe 2 dengan Komplikasi Ulkus/Gangren di Instalasi Rawat Inap RSUD Dr. Moewardi Surakarta Tahun 2015 - Hajma, Lilla Prapdhani Agni, Hidayah Karuniawati, M.Sc., Apt (2017)
Diabetes mellitus is a disease that requires long-term treatment that would otherwise be handled properly can cause complications of ulcer/gangrene. Diabetic ulcers are open sores that contained surface of the skin or mucous membranes that can be invaded by the bacteria causing the infection and need treatment with antibiotics. The need for accuracy in the selection of antibiotics intended to allow the ulcer healed quickly so it does not harm the patient. This study aims to determine the accuracy of the use of antibiotics in patients with type 2 diabetes mellitus with complications of ulcer/gangrene in RSUD Dr. Moewardi. This study is a non-experimental descriptive by observation of the patient record ulcers diabetic who underwent inpatient and get a prescription of antibiotics by comparing the list of drugs in the medical records of patients with the literature based on criteria appropriate indication, right patient, right drug and the right dosage. The study was conducted at RSUD Dr. Moewardi Surakarta. The results of the study in 21 patients with type 2 diabetes mellitus with complications of ulcer/gangrene shows the antibiotics used in RSUD Dr. Moewardi is metronidazole (4.8%), vancomycin (4.8%) and antibioticsmetronidazole combination is ceftriaxone (47 , 6%), ceftriaxone-metronidazoleclindamycin (4.8%), levofloxacin-azithromycin-ceftriaxone (4.8%), cotrimoxazole-ciprofloxacin (4.8%), metronidazole-meropenem (4.8%), ceftriaxone -metronidazol-gentamicin (4.8%), metronidazole-clindamycinciprofloxacin (4.8%), ceftriaxone-levofloxacin (4.8%), and ceftriaxonemetronidazole- ciprofloxacin (9.5%). The results of the evaluation according to criteria appropriate usage of antibiotics that is 100% accurate indication, a 100% appropriate of patient, 42.3% for drug, and 61.9% for dose.